Welcome to the Era of Fake News - Albright, Jonathan (2017)
For the news industry, information is used to tell stories, which have traditionally been organized around “facts”. A growing problem, however, is that fact-based evidence is not relevant to a growing segment of the populace. Journalists need facts to tell stories, but they need data to understand how to engage audiences with this accurate information. The implementation of data is part of the solution to countering the erosion of trust and the decay of social discourse across networked spaces. Rather than following “trends”, news organizations should establish the groundwork to make facts “matter” by shaping the narrative instead of following deceptive statements.